2016
DOI: 10.1155/2016/4130376
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Rack1 Proteins in Fungal Pathogenesis

Abstract: Pathogenic fungi cause diseases on various organisms. Despite their differences in life cycles, fungal pathogens use well-conserved proteins and pathways to regulate developmental and infection processes. In this review, we focus on Rack1, a multifaceted scaffolding protein involved in various biological processes. Rack1 is well conserved in eukaryotes and plays important roles in fungi, though limited studies have been conducted. To accelerate the study of Rack1 proteins in fungi, we review the functions of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…To a large extent, our experiments enable the analysis of the phosphorylation reactions at amino acid resolution (reliably for all phospho-peptides with AScores > 13, meaning a p -value for the phospho-site localization <0.05). Regarding the G-proteins, RACK1-homologs have been demonstrated to function as an alternative Gβ in several fungi and are well-known for their additional role as scaffolding proteins for numerous processes in eukaryotes (Ron et al, 2013; Zhang et al, 2016). In N. crassa , the RACK1 homolog cross-pathway control-2 (CPC-2) is required for proper expression of numerous amino acid biosynthetic enzymes in response to starvation for a single amino acid (Muller et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…To a large extent, our experiments enable the analysis of the phosphorylation reactions at amino acid resolution (reliably for all phospho-peptides with AScores > 13, meaning a p -value for the phospho-site localization <0.05). Regarding the G-proteins, RACK1-homologs have been demonstrated to function as an alternative Gβ in several fungi and are well-known for their additional role as scaffolding proteins for numerous processes in eukaryotes (Ron et al, 2013; Zhang et al, 2016). In N. crassa , the RACK1 homolog cross-pathway control-2 (CPC-2) is required for proper expression of numerous amino acid biosynthetic enzymes in response to starvation for a single amino acid (Muller et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have reported the potency of 8-hydroxyquinoline as a scaffold for drug design to get novel microbial bioactive derivatives (Pippi et al, 2019). It is hypothetical that the key proteins and signal transduction pathways in plant pathogenic fungi could be the targets susceptible to preservatives such as 8-HQS in microbial inhibition (Zhang et al, 2016). The adverse effects of cold storage without pulsing of cut flowers have been reported (Chore et al, 2019).…”
Section: Days Of Storagementioning
confidence: 99%
“…As a scaffold protein, RACK1 is known to regulate many cellular processes such as cell proliferation, signaling, development, migration, and apoptosis (for review [1,2]). In addition, RACK1 has increasingly been implicated in many viral, bacterial, fungal infections as well as in human diseases, including cancer, Alzheimer, Parkinson's, and alcohol addiction [9,[11][12][13][14][15]. Recent studies demonstrated that RACK1 regulates many pathogenic protozoan/microbial/fungal infections resulting in malaria [16], scarlet-like fever [11], and histoplasmosis [15].…”
Section: Introductionmentioning
confidence: 99%